Highly reversible Li2RuO3 cathodes in sulfide-based all solid-state lithium batteries. Issue 8 (14th July 2022) - Wu, Yuqi; Zhou, Ke; Ren, Fucheng; Ha, Yang; Liang, Ziteng; Zheng, Xuefan; Wang, Zhenyu; Yang, Wu; Zhang, Maojie; Luo, Mingzeng; Battaglia, Corsin; Yang, Wanli; et al.
Abstract : Highly reversible oxygen redox chemistry of Li2 RuO3 enabled by a stabilizing electrode–electrolyte interphase with sulfide solid electrolyte. Abstract : The practical application of high-capacity lithium-rich cathode materials in lithium-ion batteries has been largely restricted by severe side reactions with electrolytes. Herein, we report a highly stable lithium-rich Li2 RuO3 cathode by forming a passivating solid electrolyte interphase at the interface with a sulfide solid electrolyte such as Li6 PS5 Cl in all-solid-state lithium batteries (ASSLBs), which efficiently suppresses serious parasitic interfacial reactions and fast-increasing interfacial impedance normally observed in liquid electrolytes. The exceptionally high interfacial stability of the Li2 RuO3 /sulfide electrolyte interface contributes to a high reversible capacity of 257 mA h g −1 of Li2 RuO3 at 0.05C rate, and unprecedented cycling stability with 90% capacity retention after 1000 cycles at 1C rate. Comprehensive experimental characterizations and first-principles calculations disclose that electronically insulating interfacial reaction products forming at the interface between the Li2 RuO3 cathode and Li6 PS5 Cl facilitate the formation of a stable and passivating interphase and block the continuous side reactions. Importantly, reversible oxygen redox activity of Li2 RuO3 is well-maintained in this configuration of ASSLBs even after 600 cycles, thus the common voltage decay of the Li-rich material is also significantly reduced. These new discoveries demonstrate the critical role of interface design for achieving prolonged cycling stability of lithium-rich cathode materials.